A cost-effectiveness analysis of alternative tuberculosis control programs in rural Zambia - Chipeta, Kettie (Health Economics Unit, 2015)
This study reviewed community-based directly observed treatment and the conventional approach to tuberculosis management in order to find cost-effective approach. Both patient and health system cost data were used. Hospital cost data were collected from a mission hospital in rural Zambia for the periods 1989 and 1997. Patient cost data were collected from a sample of 50 patients in terms of time and travel costs. The cure rate was used as the measure of effectiveness. Results showed that community-based DOT is the most cost-effective approach because of its reduced costs to the patients and health system. Finally, it was also found that community-based DOT is the most viable economic option given the existing resource constraints. Suggestions for future study are offered and limitations of research are explored.